Estimación de la variabilidad genética de nueve cultivares de gladiolo con el uso de marcadores morfológicos (Repertorio Científico, 2021)
Gladiolus is a genus of bulbous plants with high ornamental value. Despite the great demand that this crop presents in Cuba, there is no variability to offer to the population and the few cultivars that are marketed are all imported. For these reasons, it is very important to start an improvement program to create new varieties with high yields under Cuban conditions and diversify demand. A genetic improvement program must start from knowing the genetic variability that exists in the available resources, in order to estimate which traits are most susceptible to improvement. The objective of this study is to determine which morphological characters contribute the most to genetic variability in gladiolus cultivars from the Liliana Dimitrova Institute for Horticultural Research and to establish the phylogenetic relationship that exists between these cultivars. Nine gladiolus cultivars were studied, all from the Netherlands, to which morphological variables recommended and used by other studies for the same purpose were measured. Descriptive statistics such as CV and SD were determined for these variables and confidence intervals were calculated using the Monte Carlo method. The variables were subjected to a principal component analysis to determine those with the greatest contribution to variability, and subsequently a dendogram was constructed that reflects the phylogenetic relationship of the 9 cultivars and the grouping of these into three groups was observed. Based on the coefficient of variation, the characters that are most susceptible to improvement due to their high genetic variability are fresh corm mass, polar corm diameter, number of bells per ear and length of the floral ear. The analysis of the main components showed that all the variables contribute to the total variability and with the cluster analysis the phylogenetic relationship of the cultivars under study was observed. Based on the previous results, it constitutes an effective basis to start a gladiolus improvement program.
Keywords: Genetic variability; Gladiolus; Plant Breeding; Phylogenetic relationship; morphological markers